Mesial Temporal Sclerosis in SCN1A-Related Epilepsy: Two Long-Term EEG Case Studies. (July 2019) - Tiefes, Anna M.; Hartlieb, Till; Tacke, Moritz; von Stülpnagel-Steinbeis, Celina; Larsen, Line H. G.; Hao, Quin; Dahl, Hans Atli; Neubauer, Bernd A.; Gerstl, Lucia; Kudernatsch, Manfred; Kluger, Gerhard J.; Borggraefe, Ingo
Patients with temporal lobe epilepsy (TLE) due to mesial temporal sclerosis (MTS) are eligible candidates for resective epilepsy surgery. We report on 2 male patients aged 4 years with suspected TLE due to MTS who were referred for presurgical evaluation. Both patients came to medical attention within the first year of life suffering from febrile status epileptici and subsequent unprovoked seizures. The following years, moderate developmental delay was present. High-resolution magnetic resonance imaging confirmed hippocampal sclerosis. Continuous EEG video monitoring revealed seizure patterns contralateral to the MTS in both patients. Genetic analysis was performed as both the clinical presentation of the patients and EEG video monitoring findings were not consistent with the presence of the hippocampal sclerosis alone and revealed de novo mutations within exon of the SCN1A gene. Resective surgical strategies were omitted due to the genetic findings. In conclusion, both patients suffered from a dual pathology syndrome with ( a ) TLE related to MTS resulting most likely from recurrent febrile status in early childhood and ( b ) Dravet syndrome, which is most likely the cause of the febrile convulsions leading to the MTS in these 2 patients.